Superhydrophobic Archwires: Bioinspired Superhydrophobic Ni–Ti Archwires with Resistance to Bacterial Adhesion and Nickel Ion Release (Adv. Mater. Interfaces 7/2019). Issue 7 (9th April 2019) - Liu, Ruoxi; Liu, Xi; Zhou, Jie; Nie, Qiong; Meng, Jingxin; Lin, Jiuxiang; Wang, Shutao
Abstract : Biomedical materials including orthodontic archwires always face great challenges, such as the adhesion of cariogenic bacteria and the release of nickel ion. In article number1801569 by Qiong Nie, Jingxin Meng, Shutao Wang, and co‐workers, the bioinspired superhydrophobic nickel‐titanium alloy archwire shows the excellent resistance of bacteria adhesion and nickel ion release by varying the contact mode between the archwires and bacteria suspension from surface contact to point contact.